Development of Electronic Archive Book in Improving Learning Outcomes of Electronic Archive Management of Office Administration Education Students, Faculty of Economics, Unimed - Sri Mutmainnah; Gartima Sitanggang; Rotua SP Simanullang; Khairani Alawiyah Matondang (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The innovative thing in this drafted Electronic Archive Management book is that it contains theory and practical steps for managing Electronic Archives based on SIKD. So that this book is expected to be used by students in practicing electronic archive storage. This research uses a research and development approach (R&D) to the Borg and Gall model with the following development steps: 1) Research and Information Collecting, 2) Planning, 3) Develop Primary Form of Product, 4) Prelimenary Field, 5) Main Product Revision, 6) Main Field Testing, 7) Operational Product Revision, 8) Operational Field Testing, 9) Final Product Revision and 10) Dissemination and Implementation. Based on the significance value of the coefficients table, a significance value of 0.000 < 0.05 was obtained, so it was concluded that the Electronic Archive Management Book variable had an effect on the student learning outcomes variable. Based on the t value: it is known that the t count value is 8.295 > t table 1.978, so it can be concluded that the Electronic Archive Management Book variable (X) has an effect on the Learning Outcome variable (Y).